Elmadağ - Didem Danış, Ebru Kayaalp (Institut français d'études anatoliennes, 2004)
The focus of this research is to analyze the social and spatial transformations of a bounded area, the neighborhood of Elmadağ, whose most noteworthy factor has been the perpetual migration flows since its emergence as a neighborhood in the 19th century. According to the authors, the functional transformation Elmadağ is currently going through needs the explanations history can provide in order to be apprehended in full. Interdisciplinary, the research blends sociological, anthropological...